2021
DOI: 10.1186/s12951-021-00950-0
|View full text |Cite
|
Sign up to set email alerts
|

Injectable stress relaxation gelatin-based hydrogels with positive surface charge for adsorption of aggrecan and facile cartilage tissue regeneration

Abstract: Background Cartilage injury and pathological degeneration are reported in millions of patients globally. Cartilages such as articular hyaline cartilage are characterized by poor self-regeneration ability due to lack of vascular tissue. Current treatment methods adopt foreign cartilage analogue implants or microfracture surgery to accelerate tissue repair and regeneration. These methods are invasive and are associated with the formation of fibrocartilage, which warrants further exploration of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…While gelMA has been evaluated for the use in cartilage regeneration, many studies rely on the use of cell lines (Zhou et al., 2018 ), animal derived cells (L. Han et al., 2017 ; M.‐E. Han et al., 2017 ; Mouser, 2018 ; Wang et al., 2021 ) or very young donors (Boere et al., 2014 ) thus making them less applicable for translational research. Other studies using human chondrocyte sources (Brown et al., 2017 ; Gu et al., 2020 ) often focus on material characterization and only superficially describe effects on the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…While gelMA has been evaluated for the use in cartilage regeneration, many studies rely on the use of cell lines (Zhou et al., 2018 ), animal derived cells (L. Han et al., 2017 ; M.‐E. Han et al., 2017 ; Mouser, 2018 ; Wang et al., 2021 ) or very young donors (Boere et al., 2014 ) thus making them less applicable for translational research. Other studies using human chondrocyte sources (Brown et al., 2017 ; Gu et al., 2020 ) often focus on material characterization and only superficially describe effects on the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach worth mentioning consists of a modified gelatin hydrogel that absorbs proteoglycans secreted by chondrocytes near the cartilage tissue in situ and quickly forms an adequate chondrocyte survival microenvironment. Wang et al evaluated this therapeutic method, and the in vivo and in vitro results showed that the hydrogels were effective and expressed efficient biocompatibility, while promoting the tissue repair of cartilage defects [54].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Internal studies show that the hydrogel structure can be well-integrated with surrounding host tissues. Wang K.-Y. et al (2021a) and others synthesized modified gelatin Gel-EPL, Gel-B, GelEPL/B using ε-poly-L-lysine, and phenylboronic acid as raw materials.…”
Section: Treatment Strategy Of Hydrogel In Advanced Osteoarthritismentioning
confidence: 99%